Facebook as a platform for narrative paragraph writing among Malaysian secondary school learners / Yong Fuk Fui - Yong, Fuk Fui (2018)
Facebook, as a social media tool, provides a platform for enhancing interaction that can possibly be exploited for language learning (Godwin-Jones, 2008) and potentially for research (Bloch, 2008). The study aims to investigate how learners use Facebook and its features to develop English narrative paragraph writing. It has been said that many Malaysian students remain weak in the English writing (Rashidah, 2005) and writing is considered the least proficient skill out of all the language skills. This qualitative study explores how learners and their teacher perceive the use of Facebook (FB) as a platform for narrative paragraph writing. Data came from the learners’ self-reports and their teacher’s diaries recorded over seven weeks. The learners’ FB pages and an end-of-the-study-open-ended-question were also gathered as additional data sources. From the thematic analysis of the qualitative data, it was revealed that Facebook can be and should be utilised as a platform for teaching and learning. This was because, according to the learners’ self-reports, Facebook could help them develop the qualitative aspects of their writing skills (vocabulary, idioms, phrases and grammar) as well as the more global perspective of narrative paragraph writing (storylines and styles of narrating a story). From the teacher’s perspective, the participants were more autonomous in their learning compared to the traditional face-to-face classroom settings. Another finding worth noting is the process of commenting (providing and receiving comments) as it was found that learners were able to be more reflective of their own work while the teacher found that it promoted self-regulation. All these findings revealed that it is highly recommended for educators to keep abreast with the current technology in order to be able to choose the appropriate online platforms with suitable writing tasks to mediate language learning.